THE ROLE OF HIGH-FIDELITY CLINICAL SIMULATION IN HEALTH EDUCATION - Ribeiro, Norberto Maciel; de Freitas, Gregório Magno de Vasconcelos; de Góis, Liliana Maria Gonçalves Rodrigues (Seven Editora, 2026)
Health education is one of the most compelling challenges for the current 21st-century generation, enriched by digital means and highly technological. Educating for health proves to be a complex process that requires pedagogical strategies that promote the construction of new knowledge. Understanding the complex phenomenon involving health education and the environments that construct new knowledge allows for an exhaustive reflection on the nature of educational processes and simultaneously constitutes an opportunity for knowledge construction mediated by specialists in active cooperation with the student. From this perspective, high-fidelity clinical simulation stands out as a pedagogical and metacognitive strategy for the development of new fundamental knowledge and skills. Thus, high-fidelity clinical simulation in health education exerts a pedagogical and innovative action by allowing the participation and cooperation of the educational community as a central figure in the entire educational process.